VD_FINDINFO HC / 2020 / 34 vom 21. Februar 2020 - VD Tribunal cantonal (2020)
MESURE PROVISIONNELLE, DOMMAGE IRRÉPARABLE, CHARGE FONCIÈRE, SERVITUDE PERSONNELLE | 2 al. 2 CC, 641 CC, 261 al. 1 CPC (CH), 264 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)